Ethical Leadership and Decision-Making in AI: Navigating Educational Management Ethics in the Digital Age - Chayanusasanee Jundon, Sippiya; Niyomves, Busara; Kaewlamai, Somboon; Pawala, Thanyachanok (Journal of Education and Learning Reviews, 2025)
Background and Aims: Management ethics in the digital age is critical for maintaining trust because leaders must ensure responsible technology use, data privacy, and fairness in AI decisions. Ethical management promotes transparency, prevents the misuse of digital tools, and ensures accountability in a rapidly changing technological landscape. This paper aims to investigate Ethical Leadership and Decision-Making in AI Methodology: This paper used peer-reviewed literature, industry reports, and authoritative sources to conduct a systematic investigation into the intersection of ethical leadership and artificial intelligence in the digital age. It identified key trends and gaps through structured data collection and thematic analysis, and then made recommendations for promoting ethical leadership in AI decision-making. Results: The finding found that addressing critical ethical issues such as bias, transparency, privacy, and employment impact is critical for responsible AI management. Bias in AI algorithms can perpetuate societal inequalities, transparency issues can impede accountability, extensive data collection raises privacy concerns, and automation has the potential to disrupt labor markets. Effective management necessitates the implementation of fairness-aware algorithms, strong data security, and proactive workforce transition strategies. Leaders must establish ethical guidelines, foster an ethical AI culture, and adhere to global standards to navigate these challenges and promote responsible AI development. Conclusion: The findings emphasize the importance of dealing with ethical issues such as bias, transparency, privacy, and employment impact to manage AI responsibly. To foster accountability and promote responsible AI development, leaders must implement algorithms that prioritize fairness, ensure data security, and establish ethical guidelines.